COMPARATIVE STUDY OF MILK WHEY PROTEINS AND PURE CYSTINE, BY MEANS OF POLAROGRAPHY - ΑΣΙΚΗΣ Ι. Χ. (Journal of the Hellenic Veterinary Medical Society, 1972)
In the present research, it is studied the proteins, albumin and globulin, concentration in the milk whey of three mammals, cow, goat and sheep, by means of the Polarographie method and existing similarities in comparison with pure cystine are pointed out. For 150 examined milk samples, it was followed the same technique of study, selected after a good deal of preliminary tests. Also, it is studied the height, up to which Polarographie wave it is risen, after heating the milk of the above mentioned animals from 72° to 100° C. It is proved that the decrease of Polarographie protein weaves height goes nearly parallel with the increase of temperature, that is related directly with the degree of denaturation of milk albumin and globulin, having as a very probable consequence, at least, the partial destruction of the SH/SS groups contained in milk proteins.